Neural Network Characterization of Reflectarray Antennas. (18th July 2012) - Freni, Angelo; Mussetta, Marco; Pirinoli, Paola
Abstract : An efficient artificial neural network (ANN) approach for the modeling of reflectarray elementary components is introduced to improve the numerical efficiency of the different phases of the antenna design and optimization procedure, without loss in accuracy. The comparison between the results of the analysis of the entire reflectarray designed using the simplified ANN model or adopting a full-wave characterization of the unit cell finally proves the effectiveness of the proposed model.